The shapes of silence writing by women of colour and the politics of testimony - Tagore, Proma 1971- (McGill-Queen's Univ. Press, 2009)
"The Shapes of Silence examines fiction, memoir, and autobiographical writing by marginalized women whose stories give voice to the gendered dimensions of colonial violence. Drawing from the insights of subaltern studies and postcolonial feminisms, Proma Tagore brings together the work of a diverse group of writers - Toni Morrison, Shani Mootoo, Louise Erdrich, M.K. Indira, Rashsundari Debi, and Mahasweta Devi. She focuses on the visceral, affective nature of their narratives and explores the way that personal and historical trauma, initially silenced, may be recorded across generations, as well as across complex national, racial, gender, and sexual lines. In emphasizing situations that cannot be summed up by clearly nameable, bounded moments of trauma, The Shapes of Silence identifies important shifts in how testimonial literature is theorized, arguing for an understanding of writing and storytelling by women of colour as crucial counter-narratives to what official colonial historicizing has left out." -- Publisher's description.